ANTIMICROBIAL ACTIVITY OF LEAF EXTRACTS OF SOME INVASIVE ALIEN PLANT SPECIES OF ASTER FAMILY AGAINST CLINICAL BACTERIA - Sahu, Anita; Devkota, Anjana (Ecoprint: An International Journal of Ecology, 2016)
Aqueous and methanolic extracts of three plants at four different concentration viz. at 50, 100, 150 and 200 mg/ml were tested on clinical bacteria using the disc diffusion method. In vitro antibacterial activity was screened by using Nutrient Agar (NA). The qualitative phytochemical analysis depicted the presence of terpenoids, saponins, alkaloids, flavonoids, carotenes and glycosides in the plants. Results showed broad spectrum antimicrobial activity against the Gram-negative and Gram-positive bacteria. The methanol extract inhibited the growth of more bacteria compared to the aqueous extract. Results from in vitro study revealed that the antimicrobial activity might have been influenced by the solubility of active compound(s) in extracting solvent. Methanol extracts were relatively more effective than aqueous extract. Out of three invasive plants studied Parthenium hysterophorus seemed more effective, for inhibiting the growth of bacterial strains with maximum zone of inhibition (24.85 mm diam.), shown against Enterococcus faecalis at a concentration of 200 mg/ml. The demonstration of activity against all these organisms had shown that all three alien invasive species; Ageratum haustonianum, Mikania micrantha and Parthenium hysterophorus can be used to produce raw materials/substances for further development of diverse antibiotics with broad spectrum of activity. ECOPRINT 23: 1-12, 2016